2009
DOI: 10.1007/s10555-009-9195-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutrophils and TNF-related apoptosis-inducing ligand (TRAIL) in bacillus Calmette–Guérin (BCG) immunotherapy for urothelial carcinoma of the bladder

Abstract: Intravesical Mycobacterium bovis bacillus Calmette-Guérin (BCG) immunotherapy is a highly effective treatment for carcinoma in situ of the bladder, as well as high-risk nonmuscle invasive urothelial carcinoma of the bladder. Despite over 30 years of clinical experience with BCG, the therapy's mechanism has remained enigmatic. Observations regarding the role of neutrophils in BCG immunotherapy have led to exciting discoveries regarding the potential role of tumor necrosis factor-related apoptosis-inducing ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…Neutrophils are significant sources of TNF-␣ and TRAIL [3,5]. However, to date, only TRAIL has been proposed to mediate the antitumor activity of BCG [6,7]. Although BCG immunotherapy is the current standard for bladder cancer therapy, relapse and resistance to BCG are common; thus, there is a need to elucidate how exactly BCG-stimulated neutrophils exert their action and to find alternative therapies to overcome resistance to BCG immunotherapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are significant sources of TNF-␣ and TRAIL [3,5]. However, to date, only TRAIL has been proposed to mediate the antitumor activity of BCG [6,7]. Although BCG immunotherapy is the current standard for bladder cancer therapy, relapse and resistance to BCG are common; thus, there is a need to elucidate how exactly BCG-stimulated neutrophils exert their action and to find alternative therapies to overcome resistance to BCG immunotherapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…17 In support of this model, it has been demonstrated that BCG treatment induces surface expression of TRAIL on neutrophils, thus arming them with the capacity to induce tumor cell death. [18][19][20] In addition, inflammatory monocytes and natural killer cells are stimulated to produce high concentrations of effector cytokines. [21][22][23] Based on data obtained in a previous observational clinical study in bladder cancer patients receiving intravesical BCG therapy as well as published experimental data, we concluded that multiple BCG treatments resulted in a "prime/boost" response for the innate immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, Bacillus Calmette–Guérin (BCG) is still the most successful bacterial agent used for superficial bladder cancer treatment [40]. BCG was introduced by Morales in 1976, based on the original development in 1921 as an attenuated strain of Mycobacterium bovis for tuberculosis vaccination.…”
Section: Recent Approaches On Bacterial Immunotherapymentioning
confidence: 99%